ANALYSIS OF THE RESULTS OF PREVENTIVE MEDICAL EXAMINATION OF PRESCHOOL CHILDREN IN THE REPUBLIC OF KARAKALPAKSTAN (2023) - Salomova F. I.; Abdirova A. M. (The Conference Hub, 2025)
Uzbekistan has achieved significant improvements in maternal and child health: for example, maternal mortality fell 1.5-fold and infant mortality 1.3-fold during 2017–2022[1]. At the same time, Karakalpakstan has introduced innovative child health measures; home-visiting nursing programs have been shown to be highly effective in early detection of child health issues[2]. This study analyzes the results of preventive medical examinations of preschool children in Karakalpakstan in 2023, including the number of children examined, the types and frequency of detected pathologies, and their distribution by organ system. We also identify organizational and methodological challenges in health screening and formulate recommendations to improve the region’s healthcare system.
Keywords: child health, preschool children, preventive medical examination, pathologies, Karakalpakstan.